Endogenous growth: A search model for new technology with applications to international trade. - Zahedi Vafa, Mohammad Hadi. (University of Ottawa (Canada), 2001)
A model in which firms carry out a sequential search to raise their technological level is formulated under the overlapping-generations framework. Technological improvements are random outcomes of a sequential search process, which is financed by the capital raised by firms. The amount of capital resources spent on searching for new technologies by a firm is endogenous and depends on the search undertaken by the firm and its capital. This model identifies some factors that affect the interactions between the search process and the production technology. The basic model is extended to that of a two-sector economy that encompasses a high-technology sector and a more traditional sector. In the extended model, capital is sector-specific. Firms in the high-technology sector can raise their technological level by engaging in R&D, while those in the traditional sector have no more prospects for improving their technological capacity. The two sectors differ from each other in terms of technological level and factor intensity. Finally, the two-sector model is extended in to the world of international trade to analyze the impact of technological change on trade in goods and capital flow.
Keywords: Economics, Theory.